Study of cell survival in non-adherent conditions - Małecki, Maciej (Contemporary Oncology/Współczesna Onkologia, 2003)
Crucial steps of the development of malignant cells include their ability to survive in non-adherent conditions. These cells can separate from solid tumors and escape from anoikis. The anoikis resistant cells do not undergo apoptosis induced by the loss cell to cell or cell to extracellular matrix contacts and may then be disseminated in the whole organism. The survival of neoplastic cells in the blood stream determines their potential ability to produce secondary tumors. The main aim of this work was to study cell survival in non-adherent conditions. Some aspects of the mitochondrial dependent apoptosis and DNA repair of the adherent and non-adherent tumor and normal cells were evaluated. The human ovarian cancer cell line, OVP 10 and human urothelial cell line, HCV-29 were used in all experiments. The studies were performed on adherent and non-adherent cells in a relatively short period of time after detachment. In contrast to non- -adherent HCV-29 cells, the non- -adherent OVP 10 cells revealed the ability to translocate cytochrom c protein from mitochondrion to cytoplasm. It is worth underlining that OVP 10 cells did not reveal the presence of caspase 3 protein. These findings may explain the low percentage of apoptosis in non- -adherent OVP 10 cells as described previously [5]. It has also been shown that non-adherent HCV-29 cells expressed the DNA double-strand break repair protein (Rad51) weaker than adherent ones, whereas the DNA mismatch repair protein (MSH-2) was of the same in the same level. The present results give new information concerning anoikis and extend knowledge about biology of tumor cells and mechanisms of metastasis formation.